Penerapan Fuzzy pada Indikator Teknikal untuk Memprediksi Trend dan Manajemen Resiko pada Pasar Forex - Sutikno Goutama; Agustinus Noertjahyana; Rolly Intan (Jurnal Infra, 2020)
Trading on the forex market (foreign exchange) is an activity that can provide large profits and convenience for traders because it does not require a physical office space and the trading process can be done anywhere. However, trading activity cannot be separated from the risk of large losses, because trader sometimes do not understand the movement of trends or having difficulties in determining the risk that must be taken. These problems make traders likely to get losses compared to gain profits. Therefore, traders need a program or expert advisor (EA) that can help to predict trends and manage market risk.Dynamic forex market movements and diversity on pair currency, often make traders confuse to read the right circumstances and determine when the right time to trade. As a solution to overcome the uncertainty in analyzing the market, one of the concepts that can be applied is fuzzy logic. This concept can help to change something which has uncertainty into a value that can be used as a reference.Results conducted on 3 technical indicators (Relative Strength Index, Stochastic Oscillator, and Moving Average Convergence/Divergence) in forex market using fuzzy logic in the form of expert advisor (EA) program shows that several expert advisor (EA) with predetermined parameters will produce appropriate stop loss output limits, which provide the largest profit of 128.04 in AUD/USD pair, 175.42 in GBP/USD pair and 250.26 in USD/JPY pair in the last 3 years.